Serviço hospitalar de limpeza e acidentes de trabalho: contribuições da enfermagem - Ceron, Marinez Diniz da Silva (2013)
This study aimed to analyze factors associated to occupational accidents with workers from the Hospital Housekeeping of a public university hospital in Rio Grande do Sul, Brazil. It is a cross-sectional study, involving 157 workers. It was used a form for socio-demographic, labor, habit, health and occupational accidents characterization, as well as an Effort-Reward Imbalance scale. Data colection was developed between March and June 2013. This study is part of the matrix project Evaluation of work and health conditions of hospital housekeeping workers , inserted in the Research Group Work, Health, Education and Nursing of Nursing Department of Federal University of Santa Maria, in the Research line Work and Management in Nursing and Health. Epiinfo 6.04 and PASW 18.0 were used on data preparation and analysis. To verify associations, it was adopted Chi-square or Fisher s Exact Test, Prevalence ration and its respective trust intervals (TI95%). Multivariate regressions were used to identify the association adjusted for confounders (p<0,25). As a result, it was evidences a prevalence of female, mean age of 39.9 years (DP=9,8), with self-referred white race and complete high school education. We observed a 33.1% prevalence of exposure to occupational stress and 17.8% of accidents at work. It was predominant sharps injuries and falls. The hands and fingers were the body parts most affected. Younger workers, those with no time for leisure, the day and those who reported insufficient number of workers at work scale were significantly associated with greater exposure to stress. After adjusting for confounding factors, it was found that workers who reported not having in-service training had higher prevalence of work injury. This research will contribute a perspective of health promotion and continuing health education, providing benefits to employees of the SHL in general.